3z-2=4z

Simple and best practice solution for 3z-2=4z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3z-2=4z equation:


Simplifying
3z + -2 = 4z
Reorder the terms:
-2 + 3z = 4z
Solving
-2 + 3z = 4z
Solving for variable 'z'.
Move all terms containing z to the left, all other terms to the right.
Add '-4z' to each side of the equation.
-2 + 3z + -4z = 4z + -4z
Combine like terms: 3z + -4z = -1z
-2 + -1z = 4z + -4z
Combine like terms: 4z + -4z = 0
-2 + -1z = 0
Add '2' to each side of the equation.
-2 + 2 + -1z = 0 + 2
Combine like terms: -2 + 2 = 0
0 + -1z = 0 + 2
-1z = 0 + 2
Combine like terms: 0 + 2 = 2
-1z = 2
Divide each side by '-1'.
z = -2
Simplifying
z = -2

You can always share this solution

See similar equations:

| -6(x-6)-2(-7x-8)=7(x+8)-1 | | 6(k-5)-(1-5k)=10k | | 6t=-52 | | (3x)(x)=192 | | (3x)(c)=192 | | 3x-5=-6x-4 | | 4-21=3x-5-2x | | 4.5q-3.6-5.8q=-2.5q-1.5 | | 4y^3=81 | | Y^2=50 | | -8y+9=-9y+6 | | -9x-21=10x+7 | | 5x+4(x-30)=63-x+3 | | -9x-21=10+7 | | 4w^2+4w+i=0 | | 4t+11=6t-13 | | 3x^3+x^2-90=0 | | -35x+12=-x-12 | | 4t=11+6t-13 | | lnx=-8 | | 5(x+3)-4=3x+2(3+x) | | -11x-3=8 | | 5y-9=3y+3 | | -17x-8=9 | | 8x+6-3x=5x+6 | | 12(2x-6)=4(6x+2) | | 4(3n-1)=(3n+2)+7 | | (4x-5)(7+x)=0 | | 4(x+3)(-x-8)=0 | | 8+3s-3=9s+6-5s | | 5(2x+3)+6=10x+21 | | (x+1)(x+8)=0 | | 7x-6=2(x+1) | | m^4+2m^2+m=0 | | b^2-17b+66=0 | | 0.7x-5.3=0.3 | | 7t+8t=135 | | 8y+3(y-6)=4(y+2)-2 | | b^3+5b^2+6b=0 | | -5(t-3)+8t=6t-9 | | 5(x+1)=25 | | 5(7x+3)-8=35x+7 | | -2(4b+3)+(9b-9)=0 | | 8x+8=8(x-6) | | 0.23y-0.8=0.13y+1-0.5y | | 3.3q-1.1-4.8q=2.5q-4.8 | | 5s-28=-46+2s | | 5x^6+10x^5-15x^4+10x^3=0 | | 2a-3a-5a=(5)2a+10 | | 12w^2-10w=(2w)3w+5 | | -37s=-74 | | X^2+4-5=0 | | 16(n+2)=4(8+4n) | | 7(7y-6)= | | t^2+2t-224=0 | | 3r-10=4+5r | | 0.18(y-8)+0.10y=0.14y-0.01(60) | | 2s-12=-14+3s | | 0.60x+0.60(60)=0.30(116) | | x^2+6=233.3x^3 | | 4x+4-8x=8-(4x+4) | | 10x-5=45x+2 | | 5x/2-x=(x/10)-(28/5) | | (x-2x)x=5x-5 | | 2x+6y=10 |


Related pages


derivative of xexprime factorisationswhat is the greatest common factor of 36 and 81quadratic solver with stepsprime factorization 45sinx cosx solveprime factorization of 216x 2y 2 graphx 1 cubed100-62y sin4xprime factorization of 873x3 solutionax b solve for x4x3 calculator2sin cosy 9y4x 3y 12p 2l 2w for lroman numeral 1995sin3602x 2y 14bsquaredwhat does gcf64-47solve for p 2l 2w7.25 x 205x-7 2-4xsimplify the square root of 180graph x 2-4xwhat is 12.5 as a decimalsolve 2x y 3prime factorization 104roman numeral of 1000000sec 2x graphfactoring calculator with steps112-80factor 3x 2 2x 2how to solve y 2x 5180-133simplify x 2y 3formula of 1 cos2xprime factorization for 1751942 roman numeralsprime factors of 2933.091prime factorization of 231factors of63what is the prime factorization of 192prime factors of 365500-164convert 49.99 to pounds67-9-1derivative of e 2tgcf calculator algebrafraction times fraction calculatorprime factorization of 792what are the prime factorization of 80prime factorization of 375prime factorization 75greatest common factor of 121prime factorization of 52log2 log349.99 to euromaths 2cd0.3 as a decimalsolve 5x2 30x 651 cos 12x87-41101 prime factorizationln15log3x 3